Populasi Planaria di lokasi Bukit Tunggul dan Maribaya, Bandung Utara - Hertien Surtikanti (Jurnal Matematika & Sains, 2004)
Planaria sp. is an organism inhabiting clean freshwater. The presence of Planaria sp. is diminishing at several locations. In order to understand the influence of environmental factors to the population of Planaria sp., field study on density and biomass of Planaria sp. has been carried out in two study locations Bukit Tunggul and Maribaya stream. These two streams have been known to be less impacted sites located of the Cikapundung River. Planaria sp. was sampled using plots 50 cm x 50 cm, to once a month in March, April and May 2002. These samples were brought to the laboratory of Ecology for density enumeration (density/m2) and biomass determination (gr/individual). Water quality parameters (dissolved oxygen, conductivity, pH, turbidity and temperature) at these two locations were measured in the field. Statistical analysis results showed that: (a) the density of Planaria sp. was significantly different (P